2014
DOI: 10.2478/s13536-014-0241-x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical properties of hydroxyapatite deposited through electrophoretic process on different sandblasted samples

Abstract: An implantable material based on titanium (Ti6Al4V) was sandblasted in order to be deposited with a thin film of hydroxyapatite. Two samples of the alloy, in a shape of a bar with 10 mm diameter and 20 mm length, were subjected to mechanical treatment. After deposition of the hydroxyapatite through electrophoresis process, the samples were analyzed by scanning electron microscopy. The nature and chemical properties of thin films formed on Ti-based substrate were investigated with electrochemical impedance spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…in the case of liquid cooling media that have a vaporization temperature lower than the surface temperature of the heattreated sample, four stages occur, depending on the temperature difference between the metal surface and the cooling medium [5][6][7]: a) instantaneous cooling of the metal surface, by sudden heating of the liquid medium by approaching the part until the vaporization temperature is reached; b) heating, which consists of the formation of a vapor coating on the sample surface and which reduces the heat exchange rate;…”
Section: Introductionmentioning
confidence: 99%
“…in the case of liquid cooling media that have a vaporization temperature lower than the surface temperature of the heattreated sample, four stages occur, depending on the temperature difference between the metal surface and the cooling medium [5][6][7]: a) instantaneous cooling of the metal surface, by sudden heating of the liquid medium by approaching the part until the vaporization temperature is reached; b) heating, which consists of the formation of a vapor coating on the sample surface and which reduces the heat exchange rate;…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxyapatite (HA) in large or small quantities is not toxic to biological cells) and is almost inactive in biological environments. Additionally, numerous studies have investigated and confirmed the excellent properties of hydroxyapatite in contact with bone tissues [15,16]. The most efficient method of enhancing the osteogenesis of Ti-based alloys in medical implants is covering them with a bioactive layer such as hydroxyapatite.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, as an alternative to conventional quenching media were tested and used for quenching the synthetic media, usually chosen from chemical waste substances obtained from paper processing, petroleum products etc. Quenching media of this type can be classified into three main groups: aqueous solutions of plastics; mixtures of different substances that forms gels; oil in water emulsions [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%